Pemanfaatan Konten Digital sebagai Upaya Pelestarian Budaya Gendang Beleq, Kelentang, dan Wayang Kulit di Desa Pesanggrahan Kecamatan Montong Gading Kabupaten Lombok Timur - Suci Yanti; Muhammad Firman Septiadi; Ayu Rokyatul Aeni; Lasmi Hardianti; Sayid Muhammad Alwi (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Indonesia possesses a highly diverse cultural heritage; however, the preservation of traditional arts is facing serious challenges amid modernization and the rapid development of digital technology. Pesanggrahan Village, Montong Gading District, East Lombok Regency, is one of the areas that still preserves three traditional arts, namely Gendang Beleq, Kelentang, and Wayang Kulit. Nevertheless, these traditional arts are confronted with several problems, including weak artist regeneration, declining performance frequency, decreasing interest among younger generations, and limited structured and accessible cultural documentation. This study aims to map the current condition of the three traditional arts, analyze the forms of digital content that have been developed as preservation media, identify opportunities, challenges, and optimization strategies for the use of digital content, and formulate practical recommendations for local cultural preservation. This study employed a descriptive qualitative approach with a single case study design. Data were collected through in-depth interviews, participatory observation, documentation, and document analysis involving artists, traditional leaders, and village youth as informants. The data were analyzed using inductive thematic analysis. The results show that Gendang Beleq, Kelentang, and Wayang Kulit still exist in the social life of the Pesanggrahan community, but they are in a vulnerable condition due to regeneration issues and declining performance vitality. On the other hand, organic digitalization initiatives have emerged through the documentation of Gendang Beleq performances on YouTube and the use of digital cultural materials in arts and culture learning at schools. This study also found that documentary videos, short-form social media content, cultural podcasts, and interactive content have the potential to become effective formats for cultural preservation, with YouTube, Instagram, TikTok, and Facebook serving as relevant platforms. However, the implementation of digitalization still faces obstacles, including low digital literacy among senior artists, limited internet infrastructure, issues related to cultural sacredness, and financial constraints. Therefore, the use of digital content has the potential to become an effective strategy for cultural preservation if supported by sustainable collaboration among artists, village youth, schools, government, and other related institutions.